Topical and oral minoxidil for hair disorders in pediatric patients: What do we know so far? - Lemes, Luciana Rodino; Melo, Daniel Fernandes; de Oliveira, Daniele Sguissardi; de La-Rocque, Marcella; Zompero, Camila; Ramos, Paulo Müller [UNESP] (Hindawi, 2020)
Minoxidil is a strong arterial vasodilator, first introduced as an antihypertensive medication. In dermatology, topical minoxidil (TMX) has been used for many types of alopecia. TMX is not FDA-approved in patients under 18 years old and there are no guidelines for its pediatric use. Low-dose oral minoxidil (OMX) has been used off-label for hair loss treatment in adults expecting to achieve better therapeutic compliance and greater clinical efficacy. However, little is known about TMX and OMX in pediatric population. the literature presented on TMX and OMX in children to date was reviewed. The terms “minoxidil”, “child”, “children”, “childhood”, and “infant” were used to perform a literature search in MEDLINE through PubMed. The search was limited to articles about humans and available in English. While 25 relevant articles were selected, duplicate titles were excluded. This article pointed out the use of minoxidil in several pediatric hair diseases. Even when used topically, dermatologists should be aware of potential risks of systemic absorption. In particular situations, OMX in very low doses may be considered. To date, there are no guidelines regarding the ideal dose or minimum age for using the drug topically or systemically.
Keywords: alopecia; childhood; children; hair disorders; minoxidil; oral minoxidil; topical minoxidil